Unrecorded Lexis in the Annotation of the Hudhaliyyin Poems by Al-Sukkari (275 AH), from the beginning of the book to the end of Al-Mu’atal Al-Hudhali’s Poetry - Adedeji, Shehu Yakubu (Journal of Arabic Language Sciences and Literature, 2024)
The research dealt with the Unrecorded Lexis in the Annotation of the Hudhaliyyin Poems by Al-Sukkari, from the beginning of the book to the end of Al-Mu’atal Al-Hudhali’s Poetry, the words and connotations contained in the explanations of the poetry, whether in the poet’s poem, the annotator’s commentary, or in his evidence, which were not recorded in the entries of Arabic dictionaries. It is a rectification on Arabic dictionaries in terms of words and semantics, to include all Arabic vocabulary used in the eras of linguistic evidence, as well as dialect words with their various connotations. It relied on the descriptive analytical method.The study reached several results, including: 1.The presence of a number of strange and dialect Arabic, and foreign words that are Arabized and borrowed at the lexical level. Out of which are 28 words and meanings there were not recorded in the Arabic dictionaries. 2.That knowing these phrases is useful in the art of lexicography, as they are cited in their appropriate entries in the comprehensive dictionary. Its knowledge and evidence are used in the work on the historical Arabic dictionary.The research recommends creating a language corpus dedicated to the Hudhayl dialect, including its words, connotations, linguistic styles, proverbs, and maxims.
Keywords: Unregistered lexis; Hudhail; Hudhail poetry; Al-Sukkari